Pengaruh Job Burnout, Kepuasan, dan Komitmen Berorganisasi Terhadap Turnover Intention Karyawan di PT Sari Indah Pembungkus Industri - Nico Gabriel Sanjaya; I Nyoman Sutapa (Jurnal Titra, 2022)
PT Sari Indah Pembungkus Industri is one of the industrial companies engaged in the production of cardboard packaging boxes. PT Sari Indah Pembungkus Industri where the turnover intention of employees continued to increase from year to year. This study aims to analyze the influence of job burnout, kepuasan kerja, and komitmen berorganisasi factors that affect employee turnover intention behavior at PT Sari Indah Pembungkus Industri so that it can be used as evaluation material for company development. The method used to conduct this research is Partial Least Square (PLS) analysis using SmartPLS version 3 software. The results of this study are job burnout, kepuasan kerja, and komitmen berorganisasi affect turnover. Employee intention at PT Sari Indah Pembungkus Industri either partially or simultaneously.